Sprint acceleration mechanics changes from children to adolescent - Rossi, J.; Slotala, R.; Samozino, P.; Morin, J.-B.; Edouard, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Sprint running is a critical performance parameter in many sports such as athletics, soccer or rugby that implies large forward acceleration. From a mechanical standpoint, previous studies showed that sprint performance is directly depending on the capacity to develop high amounts of horizontal force and power output over sprint acceleration (Morin et al. 2011). More precisely, the overall mechanical capability to produce horizontal external force during sprint acceleration is well described by the force-velocity (F-v) relationship (Morin et al. 2012; Rabita et al. 2015). This linear relationship characterizes the external mechanical limits of the entire neuromuscular system and is well summarized through the theoretical maximal horizontal force (F0) and velocity (v0) this system can develop, and the associated maximal power output (Pmax, Samozino et al. 2015). These variables represent a complex integration of numerous individual mechanical muscle properties, morphological and neural factors, but also the technical ability to apply external force effectively onto the ground (Morin et al. 2011, 2012). Therefore, determining individual F-v and P-v relationships and mechanical effectiveness during sprint propulsion is of great interest for coaches or sport practitioners. Several studies have been conducted to identify and understand the mechanism of sprint performance acceleration in subjects ranging from adult recreational to world class sprinters (Morin et al. 2011, 2012), and masters athletes (Morin et al., 2016) or between male and female runners (Korhonen et al. 2003; Slawinski et al. 2017). Surprisingly, only few studies have specifically focussed on the effect of age on sprint mechanics during growth (Papaiakovou et al. 2009). If it has been reported that age positively affects sprint performance (Papaiakovou et al. 2009), there is no information regarding sprint acceleration mechanics explaining this change in performance during the growth period of children and adolescents. Therefore, the aim of the present study was to compare sprint acceleration mechanics between children and adolescent in order to better understand the underlying mechanisms in sprint performance with age.